2019
DOI: 10.1007/s00784-019-03110-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of titanium-zirconium implants with a hydrophilic surface in patients with controlled type 2 diabetes mellitus: 2-year results from a prospective case-control clinical study

Abstract: Objective: Analyze the 2-year clinical performance of single-unit titanium-zirconium (TiZr) alloy narrow diameter (3.3 mm) dental implants with a hydrophilic surface (Straumann ® Roxolid ® , SLActive ® ) in patients with controlled type 2 diabetes mellitus (T2DM), measured using the glycated hemoglobin A (HbA1c) concentration test, compared to results in individuals without T2DM. Material and Methods:The studied sample consisted of 28 patients, 14 with T2DM (study group) and 14 without (control group). The pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…This benefit to implant integration was not found in a subsequent study with the same split‐mouth design applied to PC diabetics and non‐diabetic controls 38 . In a prospective study of WC diabetics (mean HbA1c = 7%) and non‐diabetic controls receiving modSLA implants, a 100% success and survival rate was found in both groups, despite a higher prevalence of type III bone in the group with T2DM 39,40 . The present study provides similar findings in a PC population and corroborates these results with dPROs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This benefit to implant integration was not found in a subsequent study with the same split‐mouth design applied to PC diabetics and non‐diabetic controls 38 . In a prospective study of WC diabetics (mean HbA1c = 7%) and non‐diabetic controls receiving modSLA implants, a 100% success and survival rate was found in both groups, despite a higher prevalence of type III bone in the group with T2DM 39,40 . The present study provides similar findings in a PC population and corroborates these results with dPROs.…”
Section: Discussionsupporting
confidence: 86%
“…Generally, other clinical studies have reported 100% survival rates for mod-SLA, Ti-Zr implants placed in PC patients with T2DM. [38][39][40] Aguilar-Salvatierra and coworkers reported 2-year survival rates of 96.6% and 86.3% for PC individuals with HbA1c levels ranging from 6.1% to 8% and 8.1% to 10%, respectively. 41 When comparing non-diabetic and diabetic individuals, a recent systematic review found no significant difference in implant survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…The implants used in their study had bone level shape without the machined collar such as the tissue level implants. The latter used together with bone level implants revealed a mean MBL of 0.71 ± 0.58 mm and 1.55 ± 0.46 mm, respectively assessed in a clinical trial 2 years after prosthetic loading [32]. A narrative review pointed out that the tissue level implant was positively correlated with crestal bone level maintenance as the distance between bone crest and the margin of prosthetic restoration automatically exceeds 1.5 mm, a factor listed as one of the prerogatives against the onset of peri-implant lesions [33].…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent 5-year follow-up [46] concluded that smoking had no effect on peri-implant tissues surrounding Ti-or TiZr-implants, concomitantly highlighting the role of routine oral hygiene maintenance. Also, when it comes to patients with well-controlled diabetes mellitus type 2, the prognosis for TiZr-implants seems to be equally good as for subjects with normal glycemic level [47].…”
Section: Discussionmentioning
confidence: 99%